Impact of turbulence on power production by a free-stream tidal turbine in real sea conditions. (March 2020) - Sentchev, Alexei; Thiébaut, Maxime; Schmitt, François G.
Abstract: An experiment was performed to study the power production by a Darrieus type turbine of the Dutch company Water2Energy in a tidal estuary. Advanced instrumentation packages, including mechanical sensors, acoustic Doppler current profiler (ADCP), and velocimeter (ADV), were implemented to measure the tidal current velocities in the approaching flow, to estimate the turbine performance and to assess the effect of turbulence on power production. The optimal performance was found to be relatively high ( C p  ∼ 0.4). Analysis of the power time history revealed a large increase in magnitude of power fluctuations caused by turbulence as the flow velocity increases between 1 and 1.2 m/s. Turbulence intensity does not alone capture quantitative changes in the turbulent regime of the real flow. The standard deviation of velocity fluctuations was preferred in assessing the effect of turbulence on power production. Assessing the scaling properties of the turbulence, such as dissipation rate, ε, the integral lengthscale, L, helped to understand how the turbulence is spatially organized with respect to turbine dimensions. The magnitude of power fluctuations was found to be proportional to L and the strongest impact of turbulence on power generation is achieved when the size of turbulent eddies matches the turbine size. Highlights: Performance of a tidal Darrieus type turbine is evaluated in real sea conditions. Turbulence on site is characterized by estimating scaling properties of velocity. Relation between the magnitude of power fluctuations and turbulence is found. Magnitude of power fluctuations is proportional to the integral lengthscale. Largest fluctuations of power are caused by eddies of size exceeding the turbine size.